Sperm morphology, motility, and velocity in naturally occurring polyploid European weatherfish (Misgurnus fossilis L.) - Alavi, Sayyed Mohammad Hadi; Drozd, Bořek; Hatef, Azadeh; Flajšhans, Martin (Theriogenology, 2013)
Spontaneous polyploidy has been frequently documented in various fish species. This process may lead to disruption in testicular development and function. In the present study, sperm morphology and motility, elements critical to male fertility, were characterized in the naturally occurring triploid (3n) and tetraploid (4n) European weatherfish, Misgurnus fossilis L. (Teleostei, Cobitidae) inhabiting the upper reaches of the Lužnice River in the Czech Republic. Sperm with smaller heads, shorter flagella, and a lower number of mitochondria was observed in 3n specimens compared with 4n, but no differences were observed in size of midpiece or ultrastructure of sperm. Similar to most teleosts, the European weatherfish spermatozoon lacked an acrosome and consisted of a head (containing DNA), a midpiece (containing mitochondria and proximal and distal centrioles), and a flagellum with 9 + 2 microtubular structure. Sperm velocity was significantly lower in individuals with 4n compared with 3n, whereas no difference in sperm motility was observed. The stepwise linear regression reported significant negative correlations between sperm velocity and length of sperm head (r = -0.92, P < 0.01). In conclusion, the data reported no effect of polyploidy on sperm ultrastructure and motility in the European weatherfish, although it can affect sperm velocity, possibly through differences in head size and the number of mitochondria, which provide ATP for sperm movement.
Keywords: Flagella; Sperm Motility; polyploidie; zvířata; Male; spermie; motilita spermií; flagella; Animals; hlavička spermie; máloostní; mužské pohlaví; Spermatozoa; Cypriniformes; Sperm Head; Polyploidy